Phylogeny of the tribe Archipini (Lepidoptera: Tortricidae: Tortricinae) and evolutionary correlates of novel secondary sexual structures - Dombroskie, Jason J.; Sperling, Felix A.h. (Zootaxa, 2013)
We reconstructed a preliminary phylogeny for the economically important tribe Archipini (Lepidoptera: Tortricidae: Tortricinae) based on 135 exemplar species (including four outgroups) and a combined analyses of 28S rDNA and COI DNA using maximum parsimony, maximum likelihood, and Bayesian analyses. A summary tree was produced as the majority rule consensus tree by first assembling all clades that were present in more than 50% of analyses. Based on the results of the analyses, several taxonomic changes are suggested. After mapping secondary sexual characters (SSCs), host plant breadth, and geographic distribution onto the phylogeny, we examined correspondences among these traits using two-by-two χ2 tests and ancestral character state reconstructions. Absence of SSCs was associated with decreased host plant breadth and colonization of the New World, but was not significantly associated with the presence of other SSCs. There is a strong likelihood of an Australasian origin for Archipini. We propose the synonymy of Archepandemis Mutuura with Pandemis Hübner (new synonymy); the synonymy of Cudonigera Obraztsov & Powell with Choristoneura Lederer (new synonymy); and elevation of Anaphelia Razowski, Sacaphelia Razowski, and Zelotherses Lederer to genera from subgenera of Aphelia Hübner (revised status). Epiphyas Turner, may be subordinate within Clepsis Guenée, but further study is needed to confirm this.